ME-REVIEW PEMIKIRAN PARA FILSUF ATAS KONSEPSI MASYARAKAT DALAM BUKU “REALITAS SOSIAL, REFLEKSI FILSAFAT SOSIAL ATAS HUBUNGAN INDIVIDU-MASYARAKAT DALAM CAKRAWALA SEJARAH SOSIOLOGI” - I Ketut Wisarja; Ni Nyoman Suastini (UHN IGB Sugriwa Denpasar, 2021)
Society is a unity of human life that can be mutually exclusive according to certain rules, norms, and customs that are continuous and bound by a common identity. It is inevitable that society is formed without individual interaction as the main constituent of society. Therefore, the individual is the key to the idealized form of community building. This article examines the thoughts of several philosophers working in the field of social philosophy and compares them to a complete understanding of the concept of the society they aspire to, namely a social construction that is peaceful, without fear, and far from violent behavior.